2014
DOI: 10.1177/0957926514536827
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts and classtalk: A critical discourse analysis of welfare-to-work program managers

Abstract: Historically, discourse about welfare in the United States has changed from a language of 'need' to a culture of 'dependency'. Adopting 'dependency' as a frame to construct the public opinion of welfare, workers help maintain the current punitive welfare state. In this study, we use critical discourse analysis to examine how county program managers in Ohio, USA (N = 69) use several discursive techniques to legitimate their identities as good workers while neutralizing negative connotations associated with admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…While much research, including our own, has focused on defensive and oppressive othering (Bloch ; Grazian ; Padavic ; Sumerau and Cragun ; Turgeon, Taylor, and Niehaus ), less research has examined implicit othering. According to Schwalbe et al (:424), would‐be elites and elites implicitly other subordinate groups through “mutually supportive facework that serves to maintain, vis‐à‐vis subordinate groups, a collective impression of competence and trustworthiness.” In doing so, social actors protect themselves from attributes of the backstage that may discredit them.…”
Section: Sociopolitical Context and Situated Actionmentioning
confidence: 99%
“…While much research, including our own, has focused on defensive and oppressive othering (Bloch ; Grazian ; Padavic ; Sumerau and Cragun ; Turgeon, Taylor, and Niehaus ), less research has examined implicit othering. According to Schwalbe et al (:424), would‐be elites and elites implicitly other subordinate groups through “mutually supportive facework that serves to maintain, vis‐à‐vis subordinate groups, a collective impression of competence and trustworthiness.” In doing so, social actors protect themselves from attributes of the backstage that may discredit them.…”
Section: Sociopolitical Context and Situated Actionmentioning
confidence: 99%
“…These created a narrative in which power was invested in those who guide, cajole, coach or coerce those who were non-compliant with market expectations (Connor, 2010;Turgeon et al, 2014). Here, unemployment was framed as an individual choice embedded in the psychology of the unemployed person rather than socio-economic factors (Carney, 2007;Gibson, 2009).…”
Section: Mantras Of Compliance Narratives Of Resistancementioning
confidence: 99%
“…Examination of the power of language to construct, label and discipline within the quasi-market of employment agencies and the unemployed revealed keywords, jargon and contradictory metaphors (Engels, 2006; Whitworth and Carter, 2014). These created a narrative in which power was invested in those who guide, cajole, coach or coerce those who were non-compliant with market expectations (Connor, 2010; Turgeon et al, 2014). Here, unemployment was framed as an individual choice embedded in the psychology of the unemployed person rather than socio-economic factors (Carney, 2007; Gibson, 2009).…”
Section: The Language Of Welfare Reform: a Reviewmentioning
confidence: 99%
“…However, an overlooked aspect is how these reforms look when enacted in practice (Lødemal & Trickey 2001). A large part of the literature about public welfare focuses on the discursive tactics used in policy and welfare programs (Christensen 200;Turgeon et al 2014;Wright 2016), but the topic of assumptions inscribed in welfare policies and tools, and their impact on local practices remain relatively underexplored. 1 Previously, I found that the tools used by caseworkers are designed to ensure policy compliance, while providing limited support for caseworkers helping citizens obtain an employment (Boulus-Røde 2018).…”
Section: Public Policy and Social Welfarementioning
confidence: 99%
“…Prior to the current discourse, there was a shift from language of need to a culture of dependency (Turgeon et al 2014), thus viewing benefit recipients as personally responsible for needing welfare assistance. This type of language was used by Reagan during his 1976 presidential campaign, when he coined the term 'welfare queen', in a fictional story of a Cadillac-driving 'welfare queen' (presumable African American) from Chicago, whose tax-free cash income topped USD 150,000 a year (Feagin 2000).…”
Section: Introductionmentioning
confidence: 99%